The Risk of Prior Opioid Exposure on Future Opioid Use and Comorbidities in Individuals With Non-Acute Musculoskeletal Knee Pain - Daniel I. Rhon; Suzanne J. Snodgrass; Joshua A. Cleland; Chad E. Cook (SAGE Publishing, 2020)
Objectives Due to their potentially deleterious effects, minimizing the use of opioids for musculoskeletal pain is a priority for healthcare systems. The objective of this study was to examine the risk of future opioid prescription use based on prior opioid use within a non-surgical cohort with musculoskeletal knee pain. We also examined the risk of pre-existing comorbidities on future opioid use, and the risk of prior opioid use on future comorbidities (sleep, mental health, cardiometabolic disorders). Methods Data came from the Military Health System Data Repository for 80 290 consecutive beneficiaries with an initial episode of care for patellofemoral pain from January 1, 2010 through December 31, 2011. Risk was calculated using 2 × 2 tables based on pre- and post-opioid utilization and comorbid diagnosis. Risk ratios, relative and absolute risk increases, and numbers needed to harm were calculated, all with 95% confidence intervals. Results Prior opioid use resulted in a risk ratio of 18.0 (95 CI 17.1, 19.0) and an absolute risk increase of 61.6% for future opioid use (numbers needed to harm = 2). The presence of all comorbidities (except cardiometabolic syndrome) were associated with a significant relative risk for future opioid use (RR range 1.2-1.5), but the absolute risk increase was trivial (range 0.7%-2.2%). The relative risk for a chronic pain diagnosis, traumatic brain injury/concussion, insomnia, depression, and PTSD were all significantly higher in those with prior opioid use (1.3-1.6), but absolute risk increase was minimal (1.1%-6.5%). Discussion Prior opioid use was a strong risk factor for future opioid use in non-surgical patients with knee pain. These findings show that history of prior opioid use is important when assessing the risk of future opioid use, whereas prior comorbidities may not be as important. Opioid history assessment should be standard practice for all patients with patellofemoral pain in whom an opioid prescription is considered.